Peningkatan Pembelajaran Apresiasi Sastra Melalui Pendekatan Konstruktivisme untuk Siswa SD - Harry Poerwanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This classroom action research tries to improve the teaching and learning process of literature appreciation using constructivist approach. More specifically, the constructivist approach is implemented during pre-reading, whilst-reading, and post-reading. Purposively sampled, nine fifth grade students were then categorized into fast, moderate, and slow readers based on their pre-test scores. This approach proves to increase students' scores in appreciating literary works.